2003
DOI: 10.1097/01.ju.0000067975.59772.b6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Pain and Return to Normal Activities Following Laparoscopic Donor Nephrectomy Versus Open Mini-Incision Donor Nephrectomy

Abstract: The laparoscopy group had significantly less postoperative pain and required less time to return to normal functional activities than the mini-incision group. In addition, the laparoscopic group showed significantly higher quality of life scores than the mini-incision group in 3 domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 15 publications
6
91
2
3
Order By: Relevance
“…[4][5][6][12][13][14] Morphine equivalents used in our LDN group were actually higher than that of our DL group and not different from that of the FL group. However, 62% (n = 85) of our FL patients used adjuvant epidural analgesia, which was not included in our morphine equivalent measure of pain management.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[4][5][6][12][13][14] Morphine equivalents used in our LDN group were actually higher than that of our DL group and not different from that of the FL group. However, 62% (n = 85) of our FL patients used adjuvant epidural analgesia, which was not included in our morphine equivalent measure of pain management.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies comparing LDN to a standard FL and mini-FL have found similar results in living renal donor surgery. [12][13][14][15] To our knowledge, this study represents one of the only studies that directly compare LDN with standard FL and DL approaches. Braga and colleagues examined open flank, DL and laparoscopic procedures to treat ureteropelvic junction obstruction; they also observed that the laparoscopic approach had the longest operative time, but the shortest hospital stay, which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In minimally invasive surgery alone, it has been used to describe health-related quality of life following laparoscopic cholecystectomy (33), Nissen fundoplication (34), inguinal hernia repair (35), colectomy (36) and gastric bypass (37). In the field of LLDN, Perry et al showed that patients had reached population norms in all eight SF-36 domains by 6 to 12 months (38), but this was the first study to use the SF-36 to describe the recovery process within weeks following the procedure. Our preoperative results are similar to the American age-matched reference values and normative data published by Ware et al (19) as well as the Canadian reference values published by Hopman et al (39).…”
Section: Standardized Outcomesmentioning
confidence: 99%
“…16 Urologic studies describing the use of ketorolac for postoperative pain control are limited, and none of these studies have been double-blind, randomized, placebo-controlled trials. [5][6][7][17][18][19][20][21] This is unfortunate because there can be considerable postoperative narcotic use in certain urologic populations. Lingeman et al 22 reported a mean postoperative morphine use of 33.2 mg (range, 7.5-76 mg) during a mean hospital stay of 3.2 days for patients undergoing PNL.…”
Section: Discussionmentioning
confidence: 99%